2008
DOI: 10.1111/j.1365-2702.2007.02180.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care unit staff nurses: predicting factors for career decisions

Abstract: A succinct validated instrument would help identify the important factors that predict ICU nurses' intention to leave their job, which may result in job disengagement. Predictors found in this study may be used as outcome variables for developing such an effective method of improving nurse retention in ICUs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 25 publications
3
61
0
7
Order By: Relevance
“…Studies on hospital nurses have revealed that professional satisfaction is a factor related to work effectiveness, productivity, absenteeism, quitting the job, turnover, patient safety and quality of care (2)(3) . There have been several attempts to measure professional satisfaction of nurses in Intensive Care Unit (ICU) settings (4)(5) , whilst moderate job satisfaction has been consistently reported among them (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…Studies on hospital nurses have revealed that professional satisfaction is a factor related to work effectiveness, productivity, absenteeism, quitting the job, turnover, patient safety and quality of care (2)(3) . There have been several attempts to measure professional satisfaction of nurses in Intensive Care Unit (ICU) settings (4)(5) , whilst moderate job satisfaction has been consistently reported among them (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…We should recognize conflict as a potential opportunity for improvement-as a chance to hear the ideas of others and ensure they're brought to light. 8,9 Although emotions can run high in the ICU, such tension is probably a sign that people care about their jobs and care about their patients.…”
Section: Resultsmentioning
confidence: 99%
“…Job satisfaction was strongly associated with the work environment in twenty five studies, including seven in ICU, with particular influence on intention to leave ( x = -4.25; SD 1.61; p < .01) [50] and (β = -0.28; p < .001) [51] . A study of 935 ICU nurses identified a positive association between job satisfaction and nurse leadership (r = 0.612; p < .001), nurse-physician collegiality (r = 0.454; p < .001), staffing and resource adequacy (r = 0.328; p < .001), participation (r = 0.307; p < .001), foundations for quality care (r = 0.437; p < .001) and professional advancement (r = 0.595; p < .001) [52] .…”
Section: Job Satisfactionmentioning
confidence: 99%
“…Emotional exhaustion was explored in fifteen studies, three in ICU [50,52,54] . A significant association was consistently reported between the level of emotional exhaustion, or burn out, by nursing staff.…”
Section: Emotional Exhaustionmentioning
confidence: 99%